2020
DOI: 10.1002/2050-7038.12676
|View full text |Cite
|
Sign up to set email alerts
|

Research on the control strategy of energy storage participation in power system frequency regulation

Abstract: Large-scale wind power integrated the power system may result in a challenge for frequency regulation because of the variable nature of wind. Energy storage system (ESS) is an effective measure against the challenge of frequency regulation caused by wind power. Aiming to solve the problem that the response time of traditional turbines can hardly meet frequency regulation demand, this article proposes a strategy for ESS which can adaptively adjust the output coefficient of ESS according its state of charge (SOC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…In recent years, with the high penetration of wind and solar renewable energy in the power grid and the power fluctuation caused by the strong randomness and intermittence of renewable energy has aroused considerable attention [1]. Owing to the responding time delay and the insufficient ramp rate, conventional generation has difficulty following the rapid power variation in renewable energy, and the incurred instability issue of system frequency cannot be ignored any longer [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, with the high penetration of wind and solar renewable energy in the power grid and the power fluctuation caused by the strong randomness and intermittence of renewable energy has aroused considerable attention [1]. Owing to the responding time delay and the insufficient ramp rate, conventional generation has difficulty following the rapid power variation in renewable energy, and the incurred instability issue of system frequency cannot be ignored any longer [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Literature [14] investigated the performance of battery energy storage participating in the frequency regulation of the all-island Irish transmission system, and the results showed that sufcient capacity of battery energy storage can reduce grid frequency fuctuations efectively. Te fuzzy theory approach was used to study the frequency regulation strategy of battery energy storage in the literature [15], and an economic efciency model for frequency regulation of battery energy storage was also established. Literature [16] proposes a method for fast frequency regulation of battery based on the amplitude phase-locked loop.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al proposed a review that highlights the recent research on the control strategy of EESs contribution in power system frequency regulation. 26 A control on the ESSs is proposed to perform a frequency regulation during wind speed variation. 27 The interest in improving the lifespan of storage devices has attracted the attention of many researchers.…”
Section: Introductionmentioning
confidence: 99%